Slowly Rotating Black Holes with Nonlinear Electrodynamics - S. H. Hendi; M. Allahverdizadeh (Advances in High Energy Physics)
We study charged slowly rotating black hole with a nonlinear electrodynamics (NED) in the presence of cosmological constant. Starting from the static solutions of Einstein-NED gravity as seed solutions, we use the angular momentum as the perturbative parameter to obtain slowly rotating black holes. We perform the perturbations up to the linear order for black holes in 4 dimensions. These solutions are asymptotically AdS and their horizon has spherical topology. We calculate the physical properties of these black holes and study their dependence on the rotation parameter a as well as the nonlinearity parameter β. In the limit β→∞, the solution describes slowly rotating AdS type black holes.